Dissolution of crosslinker from alginate beads / Siti Juwahir Jumi - Jumi, Siti Juwahir (2008)
The influence of microwave on dissolution media and their effects on calcium release properties from alginate beads was investigated. The beads were prepared by an extrusion method with sulfanilamide, sulfamerazine and sulfathiazole as model drugs. Deionized water was used as dissolution medium, either as untreated water or treated water by microwave at 80 W for 37.5 min or at 300 W for 10 min. The profiles of calcium dissolution were determined by dissolution testing and atomic absorption spectrophotometry assay. Sulfanilamide-alginate beads gave the highest rate of Ca2+ release when untreated water was used as dissolution medium. Sulfamerazine-alginate beads gave the highest rate of Ca2+ release for water treated at 80W, while sulfathiazole-alginate beads gave the highest rate of Ca2+ release when water treated at 300 W was used. This could be due to different acidic level and energetic status among these dissolution media.